2009
DOI: 10.2169/internalmedicine.48.1741
|View full text |Cite
|
Sign up to set email alerts
|

Acute Lung Injury Review

Abstract: The first report of acute respiratory distress syndrome (ARDS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
215
0
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(235 citation statements)
references
References 40 publications
6
215
0
14
Order By: Relevance
“…This proinflammatory response will ultimately induce pulmonary circulation capillary leakage which will lead to non-cardiogenic pulmonary edema, hypoxemia, type II pneumocyte hyperplasia, and neutrophil infiltration. This stage of the disease is generally followed by increased fibroproliferation and hyaline membrane formation; depending on the patient, these gross pathological changes may progress or resolve [13]. Unfortunately, risk factors to identify patients at high risk for ARDS development are still matter of research [14].…”
mentioning
confidence: 99%
“…This proinflammatory response will ultimately induce pulmonary circulation capillary leakage which will lead to non-cardiogenic pulmonary edema, hypoxemia, type II pneumocyte hyperplasia, and neutrophil infiltration. This stage of the disease is generally followed by increased fibroproliferation and hyaline membrane formation; depending on the patient, these gross pathological changes may progress or resolve [13]. Unfortunately, risk factors to identify patients at high risk for ARDS development are still matter of research [14].…”
mentioning
confidence: 99%
“…Disruption of this vascular barrier induced by inflammatory agonists, such as IL-1b, TNF-a, and LPS, and by excessive mechanical stress, such as produced by shear stress or mechanical ventilation, leads to potentially lethal physiological dysfunction, such as hypoxemia and severe lung edema, which are hallmarks of acute inflammatory lung injury (ALI) (1)(2)(3). We previously demonstrated that MYLK, the gene encoding the critical cytoskeletal effector myosin light chain kinase (MLCK), is a compelling candidate gene in inflammatory lung injuries with critical modulation of vascular EC barrier integrity such as ALI and asthma (4)(5)(6).…”
mentioning
confidence: 99%
“…At present, ALI and acute respiratory distress syndrome are two types of respiratory diseases with high fatality rates (Maybauer et al, 2006;Tsushima et al, 2009). Sepsis can lead to the development of ALI (Xue et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The CLP method was used to create the ALI-sepsis rat model (Tsushima et al, 2009). The rats were anesthetized using 6% chloral hydrate (400 mg/kg).…”
Section: Modeling and Treatmentmentioning
confidence: 99%